Harnessing genomics to improve health in the Eastern Mediterranean Region - an executive course in genomics policy - Singer Peter A; Rab Mohammed; Acharya Tara; Daar Abdallah S (BMC, 2005)
Abstract Background While innovations in medicine, science and technology have resulted in improved health and quality of life for many people, the benefits of modern medicine continue to elude millions of people in many parts of the world. To assess the potential of genomics to address health needs in EMR, the World Health Organization's Eastern Mediterranean Regional Office and the University of Toronto Joint Centre for Bioethics jointly organized a Genomics and Public Health Policy Executive Course, held September 20th-23rd, 2003, in Muscat, Oman. The 4-day course was sponsored by WHO-EMRO with additional support from the Canadian Program in Genomics and Global Health. The overall objective of the course was to collectively explore how to best harness genomics to improve health in the region. This article presents the course findings and recommendations for genomics policy in EMR. Methods The course brought together senior representatives from academia, biotechnology companies, regulatory bodies, media, voluntary, and legal organizations to engage in discussion. Topics covered included scientific advances in genomics, followed by innovations in business models, public sector perspectives, ethics, legal issues and national innovation systems. Results A set of recommendations, summarized below, was formulated for the Regional Office, the Member States and for individuals. • Advocacy for genomics and biotechnology for political leadership; • Networking between member states to share information, expertise, training, and regional cooperation in biotechnology; coordination of national surveys for assessment of health biotechnology innovation systems, science capacity, government policies, legislation and regulations, intellectual property policies, private sector activity; • Creation in each member country of an effective National Body on genomics, biotechnology and health to: - formulate national biotechnology strategies - raise biotechnology awareness - encourage teaching and training of biotechnology - devise integration of biotechnology within national health systems. Conclusion The recommendations provide the basis for a road map for EMR to take steps to harness biotechnology for better and more equitable health. As a result of these recommendations, health ministers from the region, at the 50th Regional Committee Meeting held in October 2003, have urged Member States to establish national bodies of biotechnology to formulate a strategic vision for developing biotechnology in the service of the region's health. These efforts promise to raise the profile of genomics in EMR and increase regional cooperation in this exciting new field.